The Economic Impact of Minor Forest Produce Scheme of Tribals in Kariyalur Village on Kalvarayan Hills - Yogesh, S; Govindaraj, K (Sakha: Multidisciplinary Journal of Science, Art & Technology, 2026)
This study examines the economic impact of the Minor Forest Produce (MFP) Scheme implemented by the Ministry of Tribal Affairs among the tribal community of Kariyalur village in the Kalvarayan Hills. The scheme ensures Minimum Support Price (MSP) for forest products to prevent exploitation by middlemen and improve tribal livelihoods. In Kariyalur, Malayali tribes collect products such as honey, soap nut, amla, tamarind, and broom grass for income. The study finds that the scheme has improved economic conditions and market access, though seasonal availability and migration for alternative work remain challenges. Overall, the MFP scheme has contributed positively to the socio-economic development of the tribal community.
Keywords: Minor Forest Produce (MFP); Minimum Support Price (MSP); Tribal Economy; Kariyalur; Kalvarayan Hills; Malayali Teibes; Forest Rights Act; Livelihood Development